Reflecting Reality: exploring body dysmorphic disorder in young social media enthusiasts - a cross-sectional study - Imtiaz, Musfirah; Fatima, Mishkat; Mansoori, Naveed; Intikhab, Hadiqa; Hamza, Muhammad Ali; Habib, Ahmad Amir; Ahmed, Saim Saad; Mubeen, Syed Muhammad (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the frequency of body dysmorphic disorder and its determinants among young social media users in a cosmopolitan setting, and to explore the association of the disorder with the utilisation of different social media applications. Method: The cross-sectional study was conducted from August to December 2023 after approval from the ethics committee of the Hamdard College of Medicine and Dentistry, Karachi, and comprised active social media users aged 15-28 years. Data was collected the self-reported Body Dysmorphic Disorder Questionnaire. Data was analysed using SPSS 24. Results: Of the 709 participants, 399(56.3%) were females. The overall mean age of the sample was 19.5±2.3 years. The majority of participants were single 644(90.8%) and had attained education up to high school 621(87.5%). Snapchat was being used by 180(25.4%) subjects, followed by Instagram 96(13.5%), Facebook 96(13.5%), Youtube 101(14.2) and Twitter 67(9.4%). Body dysmorphic disorder was found in 45(6.3%). The majority 513(72.4%) agreed that social media greatly influenced their appearance. Conclusion: There was a significant association between heightened social media usage and exacerbated body dysmorphic disorder symptoms. Keywords: Body dysmorphic disorder, Social media, Body image, Young adults.